Penerapan Pembelajaran Berbasis Masalah untuk Peningkatan Kemampuan Penalaran Matematis Siswa Kelas 8 SMP Al-Muhajirin Purwakarta - Siti Maryam Nurhasanah (Universitas Maritim AMNI Semarang, 2024)
This research was aimed at analyzing the enhancement of students' mathematical reasoning abilities through problem-based learning. The experimental design was pre-post control group design. The research population was all junior high school student of SMP Al-Muhajirin Purwakarta. The research sample was taken randomly, was the class VIII C students as the experimental group who participated in instruction with problem-based learning and the other class VIII D as control group who participated in instruction with conventional learning. Data was collected through test and questionnaires. The statistical analysis used is the Gain test for the results of students' mathematical reasoning ability tests. The analysis of gain score showed that the enhancement of students’ abilities who participated in instruction with problem-based learning was better than those who participated in instruction with conventional learning. Problem-based learning in mathematics lessons shows a positive response which shows that students like the method used.